Succination inactivates gasdermin D and blocks pyroptosis - Humphries, Fiachra; Shmuel-Galia, Liraz; Ketelut-Carneiro, Natalia; Li, Sheng; Wang, Bingwei; Nemmara, Venkatesh V; Wilson, Ruth; Jiang, Zhaozhao; Khalighinejad, Farnaz; Muneeruddin, Khaja; Shaffer, Scott A; Dutta, Ranjan; et al. (Science (American Association for the Advancement of Science), 2020)
Activated macrophages undergo a metabolic switch to aerobic glycolysis, accumulating Krebs' cycle intermediates that alter transcription of immune response genes. We extended these observations by defining fumarate as an inhibitor of pyroptotic cell death. We found that dimethyl fumarate (DMF) delivered to cells or endogenous fumarate reacts with gasdermin D (GSDMD) at critical cysteine residues to form S-(2-succinyl)-cysteine. GSDMD succination prevents its interaction with caspases, limiting its processing, oligomerization, and capacity to induce cell death. In mice, the administration of DMF protects against lipopolysaccharide shock and alleviates familial Mediterranean fever and experimental autoimmune encephalitis by targeting GSDMD. Collectively, these findings identify GSDMD as a target of fumarate and reveal a mechanism of action for fumarate-based therapeutics that include DMF, for the treatment of multiple sclerosis.